Influence Of Hotel Enterprises’ Social Cultural Practices On Community Empowerment Along The Coastal Tourism Circuit In Kenya - Ikwaye, Samwel Oriyama; Senaji, Thomas Anyanje; Orero, Risper Awiti; Gesage, Methusellah Bichage (Advances in Social Sciences Research Journal, 2019)
The study sought to assess the influence of socio-cultural practices on community empowerment along the coastal tourism circuit in Kenya. Data was obtained from 210 respondents who included hotel managers, employees from the local community, suppliers of goods and services to the enterprises including beach operators as well as civic leaders from Mombasa, Kwale and Kilifi counties. Hotel managers, employees, suppliers and beach operators completed a self administered questionnaire while civic leaders were interviewed. Results showed that socio-cultural practices adopted by the hotel enterprises influenced community empowerment, the influence of promotion of local heritage being significant. At the same time, it was illustrated that social innovation partially mediates the influence of the practices on community empowerment. Based on the findings, the study recommends enhanced adoption of elements of preservation of local culture and adherence to legal frame work to improve on the influence of socio-cultural practices on community empowerment. Lastly, it recommends enhanced adoption of elements of social innovation so as to improve its mediating effect.